The efficacy of mycophenolate mofetil in treating Takayasu arteritis: a systematic review and meta-analysis - Dai, Danping (Rheumatol Int, 2017)
The purpose of this study is to assess the effectiveness of mycophenolate mofetil (MMF) in treating Takayasu arteritis (TA) patients. Embase, Cochrane Library, Pubmed, Clinicaltrials. Gov and three Chinese literature databases (VIP, CNKI, WanFang) were searched; randomized-controlled trials and observational studies that compared the efficacy before and after treatment with MMF were included. The efficacy outcomes were disease activity, the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) values and steroid dosage. The results were expressed as mean differences with 95% confidence intervals. Compared with the baseline, there were significant reductions in the ESR (−14.92 [25.35, −4.48]), CRP values (−12.99 [−23.29, −2.68]) and the steroid dosage (−17.64 [−24.89, −10.4]) after the addition of MMF, and the disease tended to stabilize. Therefore, MMF might be an alternative immunosuppressive drug for TA for the control of disease activity and to taper the steroid dosage. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00296-017-3704-7) contains supplementary material, which is available to authorized users.